2018
DOI: 10.1007/s00246-018-1880-1
|View full text |Cite
|
Sign up to set email alerts
|

The Pulmonary Artery in Pediatric Patients with Marfan Syndrome: An Underestimated Aspect of the Disease

Abstract: Aortic root dilatation and its complications are known to be the most important and life limiting features in patients with Marfan syndrome (MFS). Since monitoring of patients, preventive medical and surgical treatments are available nowadays, other MFS pathologies are becoming more relevant for the outcome of the disease. Main pulmonary artery (MPA) dilatation is a cardiac finding, which has not been fully investigated in children. Due to the similarities in tissue composition of the aortic and pulmonary root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The literature search revealed 2341 de‐duplicated records, of which 289 were read in full. After the application of the inclusion criteria, 92 papers were included in the present review …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search revealed 2341 de‐duplicated records, of which 289 were read in full. After the application of the inclusion criteria, 92 papers were included in the present review …”
Section: Resultsmentioning
confidence: 99%
“…Several papers reported on mitral valve prolapse. Meanwhile, one study showed the prevalence of main pulmonary artery dilatation and its association with the occurrence of aortic root diameter, mitral valve prolapse and systemic manifestations of Marfan syndrome compared to patients without main pulmonary artery dilatations . A trial with children with no previous aortic surgeries or dissections studied the prevalence of arrhythmias in relation to clinical and echocardiographic factors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Stark and co-workers also found that dilated PA diameters on echocardiography in children are associated with an earlier occurrence of aortic dilatation, mitral valve prolapse, and systemic manifestations of MFS. In conclusion, there seems to be an association between pulmonary artery dimensions and aortic root involvement in Marfan patients, but longitudinal data are lacking [20].…”
Section: Discussionmentioning
confidence: 99%
“…Dilatation of the main pulmonary artery, 'in the absence of valvular or peripheral pulmonic stenosis, before the age of 40 years' was a diagnostic criterion of Marfan syndrome in the first Ghent nosology, but it was removed from the list of diagnostic signs [44] in the revised nosology due to the lack of diagnostic specificity [16,29]. The prevalence of pulmonary artery dilatation ranges between 8% and 16% in children [20,45] and 37% and 74% in adults with Marfan syndrome [20,44,46]. In addition, the pulmonary valve was shown to exhibit echocardiographic signs of cusp prolapse in 6% children and in 4% adults with Marfan syndrome, as well as of mild pulmonary regurgitation in 11% children, and 6% adults with Marfan syndrome [47].…”
Section: Pulmonary Valve Diseasementioning
confidence: 99%